ETHNO-CULTURAL IDENTIFICATION IN THE CONTEXT OF MODERN SOCIETY - Попова, Галина Семеновна (Science and Innovation Center Publishing House, 2013)
The aim of the article is the study of cultural peculiarities of ethnical identity on the example of the Sakha (Yakut) people. The author also makes research on the processes of identification in present ethno-cultural and social conditions. Because the process of identification has local cultural peculiarities seen on mental level, it is necessary to count them in inter-personal and inter-cultural communication in the present socio-cultural space. Based on the duality and triple identity of a Sakha person who has three-part soul Kut, the author shows her own way of classification of identity types. The author suggests a new type of identity named as “creative identity” and introduces a notion of ethno-cultural identity. Having done the analyses of peculiarities of ethno-cultural identity the author results in claiming that all ethnicities have “human”-level identity and that for adequate communication it is necessary to “humanize” a person. DOI: http://dx.doi.org/10.12731/2218-7405-2013-2-30 Целью статьи является рассмотрение особенностей этнической идентичности на примере культуры саха, этапов и уровней процесса идентификации в современных этнокультурных и социальных условиях. Поскольку процесс идентификации имеет локальные культурные особенности, происходящие на ментальном уровне, их учет в современном социокультурном пространстве актуален. Указывая на дуальность и тройственность идентичности человека (согласно трем cубстанциям Кут), автор представляет разработанную типологию этнической идентичности, предлагает новый тип идентичности под условным названием «творческая» идентичность, расширяет смысловой контекст понятия этнокультурной идентичности. В результате проведенного междисциплинарного анализа предмета исследования автор статьи приходит к выводу о том, что всем этносам присуща идентичность «человеческого» уровня и для успешной социокультурной коммуникации необходимо «очеловечивание» человека.DOI: http://dx.doi.org/10.12731/2218-7405-2013-2-30